Effect of trituration on thermal degradation of lactose using thermogravimetric analysis - Surana, Vidhi; Shukla, Richa; Jain, G.L.; Gupta, V.K. (British Homeopathic Journal, 1995)
The effect of trituration on thermal degradation of lactose (sugar of milk) was studied using a thermogravimetric analyser. A correlation between the rate of degradation with increased potency observed up to 600°C suggests that the vehicle plays an important role in the bioavailability of the drug. Comparison was also made between machine and hand triturated lactose. For lower potencies (up to the 2x) machine triturated lactose was found to degrade faster than hand triturated lactose, whereas at higher potencies hand triturated lactose showed faster degradation as compared to machine triturated lactose.
Keywords: Lactose vehicle; Thermal analysis; Trituration; Potency; Degradation; Bioavailability